A COMPARATIVE ANALYSIS OF THE TAHLILI AND MAUDHU’I METHODS IN QURANIC STUDIES - Sofian Effendi (STAI Asy-Syukriyyah, 2026)
The interpretation of the Holy Quran, as a foundational text in Islam, has been approached through diverse methodologies throughout history. Among the prominent methods in contemporary Quranic studies are the Tahlili (analytical) and Maudhu’i (thematic) approaches. This study undertakes a comprehensive comparative analysis of these two significant methods, examining their definitions, historical evolution, key characteristics, inherent strengths, and limitations. By employing a qualitative descriptive literature study methodology, this research synthesizes information from a broad spectrum of scholarly sources including academic journals, critical essays, and authoritative texts, thereby providing a nuanced understanding of each method. The findings reveal that the Tahlili approach is characterized by its meticulous verse-by-verse examination, offering a detailed and systematic interpretation that pays close attention to linguistic, contextual, and historical details. In contrast, the Maudhu’i approach adopts a topic-centric framework, enabling interpreters to draw thematic connections across different sections of the Quran, which can be particularly useful for addressing contemporary issues and deriving lessons for modern society. While both methods have distinct contributions to the field of Quranic exegesis, this study also identifies potential drawbacks, such as the risk of fragmentation in the analytical method and possible oversimplification in the thematic approach. Ultimately, this comparative analysis contributes valuable insights for researchers and students in Islamic studies, highlighting the importance of methodological plurality in deepening our understanding of the Quran